Pendampingan Pemanfaatan Legalitas Usaha (P-IRT) dalam Mendukung Kapasitas dan Keberlanjutan UMKM di Kelurahan Kelun, Kota Madiun - Juliyanti, Wiwin; Apriyanti; Fatriya Adamura; Dedy Richi Rizaldy; Donna Agnesia (Jurnal Pengabdian Masyarakat "Wiryakarya", 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the food sector play an important role in local economic development; however, many still face challenges in utilizing business legality to enhance business capacity and sustainability. One important form of business legality for food-based MSMEs in Indonesia is the Home Industry Food Production Permit (P-IRT), which functions not only as an administrative requirement but also as a guarantee of food safety and a means to increase consumer trust. This community service activity aims to assist MSMEs in utilizing business legality (P-IRT) as part of strengthening business capacity and sustainability. The activity was conducted from September 20 to November 5, 2025, involving several food-based MSMEs in Kelurahan Kelun, Madiun City, with one main partner being an MSME owned by Mrs. Riyanto, which produces P-IRT-certified traditional herbal drinks, wingko babat, and pecel chili sauce. The method applied was a participatory assistance approach through education on the utilization of P-IRT, adjustment of product labels in accordance with P-IRT standards, and strengthening business identity through simple branding. The results indicate an improvement in MSME owners understanding of P-IRT as an instrument to support business professionalism, reflected in improved product labeling and business identity. This activity is still at the capacity-building stage and has not yet reached the implementation of advanced development or quantitative impact measurement.